DAYA TERIMA DAN ZAT GIZI PERMEN JELI DENGAN PENAMBAHAN BUBUK DAUN KELOR (MORINGA OLEIFERA) - Putri Safrida Rahmawati; Annis Catur Adi (Media Gizi Indonesia, 2016)
Moringa oleifera is local plant rich in nutrients, unfortunately its utilization as a foodstuff is limited. In order to maximize the absorbtion of nutrients inside moringa, it should be made as favor food enjoyed by the people such as jelly candy. This research was conducted to evaluate organoleptic properties and nutritional value (energy and â-caroten) of jelly candy formulated with Moringa leaves powder. Using Comlpetely Randomized Design with 6 times repetition in 4 formulas which are 1 controlled formula and 3 modifi ed formulas (F1, F2, and F3), jelly candy then tested to 32untrained panels. Treatment given in this study was by adding 2%, 4%, and 6% moringa leaves powder into jelly candy formula. Data was analyzed descriptively and statistically using Kruskal Wallis and Mann Whitney test to fi nd out the difference pair. Recommended formula was chosen by counting the highest mean score of the sensory evaluationtest. The result of sensory evaluation showed that Moringa Jelly Candy was generally accepted with category “like”. However, jelly candy with lowest level of Moringa leaves powder (F1) was most acceptable in terms of color, odor, texture, and fl avor. Statistical analysis showed that the scores of color, odor, and texture were not signifi cantly different (p > 0.05) and fl avor was (p < 0.005) which means that by adding moringa leaves powder into jelly candy formula only infl uence the fl avor of jelly candy. Recommended jelly candy formula is F1 with nutritional analysis showed that per 100 g of jelly candy contains 205,8 kcal and 0.178 mcg of B -caroten.Keywords: moringa leaves powder, sensory evaluation, Moringa oleifera, jelly candy